Permian/Triassic megaspores of Otynisporites (Fuglewicz) Karasev et Turnau, 2015: Diversity, botanical affinity, and stratigraphic significance - Zavialova, Natalia; Karasev, Eugeny; Schneebeli-Hermann, Elke; Li, Wenben (Review of Palaeobotany and Palynology, 2025)
Megaspores of Otynisporites eotriassicus, O. tuberculatus, and O. maculosus from the latest Changhsingian-early Induan of the Moscow Basin of Russia, O. eotriassicus from the Induan of the Kap Stosch subbasin of East Greenland, and O.? tarimensis, and Otynisporites? sp. from the Middle Triassic of the Tarim Basin of China were studied using light, scanning and transmission electron microscopy. The general morphology and sporoderm ultrastructure of all specimens prove their affinity with heterosporous lycopsids, but they are unexpectedly variable in details of the sculpture and ultrastructure. Megaspores of Otynisporites? sp. and O.? tarimensis differ significantly from the other studied megaspores and probably were produced by a different heterosporous lycopsid. Three morphological groups are distinguished within O. eotriassicus. Multilamellated zones are found only in O. tuberculatus and (much less distinct) in O. maculosus, that leads to the necessity to re-evaluate the phylogenetic value of this character. Analysis of morphology, stratigraphic and geographic ranges of earlier reports of Otynisporites shows that confirmed findings are confined to the latest Changhsingian-Induan, with O. tuberculatus and O. maculosus sharing the same stratigraphic range as O. eotriassicus. The geographic distribution shows that Otynisporites-producing plants grew under a moderately warm climate, in the middle latitudes. A comparison with the composition of palynological assemblages from megaspore-containing deposits implies that parent plants of O. eotriassicus, O. tuberculatus, and O. maculosus more probably produced trilete cavate microspores, Lundbladispora might be a counterpart for O. eotriassicus, whereas parent plants of O.? tarimensis and Otynisporites? sp. more probably produced monolete microspores.